Economic conditions and populist radical right voting: The role of issue salience. (December 2021) - Sipma, Take; Berning, Carl C.
Abstract: In this article, we show with the European Election Study from nine Western European countries that issue salience of the economy and immigration contributes to our understanding of the puzzling relation between economic conditions and populist radical right support. In countries with relatively weak or worsening economic conditions, the economy is considered more salient, whereas immigration loses salience – also compared to other issues. Voters who perceive the economy as most important problem are less likely to opt for the populist radical right than people who perceive immigration or even other issues as most important. Populist radical right parties appear to not only win votes on the immigration issue, they also lose votes on the economic issue. Finally, in contrast to actual economic conditions, negative perceptions of the economy increases populist radical right voting, despite stronger salience of the economy and partly due to stronger salience of immigration compared to other issues.